1988
DOI: 10.1128/jb.170.12.5416-5422.1988
|View full text |Cite
|
Sign up to set email alerts
|

marA locus causes decreased expression of OmpF porin in multiple-antibiotic-resistant (Mar) mutants of Escherichia coli

Abstract: Mar (multiple antibiotic resistant) mutants of Escherichia coli express chromosomally mediated resistance to a variety of structurally unrelated hydrophilic and hydrophobic antibiotics. Insertion of transposon Tn5 into the marA locus at min 34.05 on the chromosome completely reverses the Mar phenotype (A. M. George and S. B. Levy, J. Bacteriol. 155:531-540, 1983). We found that among changes in the outer membrane of Mar mutants, porin OmpF was greatly reduced, although Mar mutants were more resistant than cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
213
0
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(231 citation statements)
references
References 31 publications
12
213
0
3
Order By: Relevance
“…Resistance to antibiotics is not a known role for RpoS so the argument above-that mutations are less selected when RpoS is needed in stress resistance-does not hold readily. However, previous studies have shown that the major outer membrane porin through which chloramphenicol transverses in E. coli is OmpF (Harder et al 1981;Cohen et al 1988Cohen et al , 1989. RpoS negatively influences ompF transcription (Liu and Ferenci 2001); therefore loss of RpoS would be a disadvantage as high outer membrane permeability to antibiotics would be a liability and hence provide an indirect F sp contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to antibiotics is not a known role for RpoS so the argument above-that mutations are less selected when RpoS is needed in stress resistance-does not hold readily. However, previous studies have shown that the major outer membrane porin through which chloramphenicol transverses in E. coli is OmpF (Harder et al 1981;Cohen et al 1988Cohen et al , 1989. RpoS negatively influences ompF transcription (Liu and Ferenci 2001); therefore loss of RpoS would be a disadvantage as high outer membrane permeability to antibiotics would be a liability and hence provide an indirect F sp contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance in these cases depends in part on the elevated synthesis of micF RNA (5,8), an antisense transcript that destabilizes the ompF mRNA (2) encoding a major porin of the outer membrane (25). Several oxidative stress genes are also transcriptionally activated by both the mar and the soxRS systems: sodA and zwf, as noted above, as well as the soil71l9 locus (21) and the genes encoding two other, unidentified oxidative stress proteins (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Exponentially growing cultures in Luria broth (22) without NaCl were harvested at an A565 of 0.8 to 1.0. Total RNA was isolated by the method of Cohen et al (9). A 20-,ug sample of total RNA was denatured with formaldehyde and formamide and subjected to electrophoresis in 1.2% agarose gels containing 2.2 M formaldehyde (22).…”
Section: Methodsmentioning
confidence: 99%